Hydrothermal Preparation of Visible-Light-Driven N-Br-Codoped TiO2 Photocatalysts - Yonggang Sheng; Yao Xu; Dong Jiang; Liping Liang; Dong Wu; Yuhan Sun (International Journal of Photoenergy)
Using a facile hydrothermal method, N-Br-codoped TiO2 photocatalyst that had intense absorption in visible region was prepared at low temperature (100°C), through a direct reaction between nanocrystalline anatase TiO2 solution and cetyltrimethylammonium bromide (CTAB). The results of X-ray photoelectron spectroscopy (XPS) showed the existence of N-Ti-N, O-Ti-N-R, Ti3+ (attribute to the doped Br atoms by charge compensation), and TiOxNy species, indicating the successful codoping of N and Br atoms, which were substituted for lattice oxygen without any influence on the crystalline phase of TiO2. In contrast to the N-doped sample, the N-Br-codoped TiO2 photocatalyst could more readily photodegrade methylene blue (MB) under visible-light irradiation. The visible-light catalytic activity of thus-prepared photocatalyst resulted from the synergetic effect of the doped nitrogen and bromine, which not only gave high absorbance in the visible-light range, but also reduced electron-hole recombination rate.